PERILAKU SEKSUAL TRANSGENDER (Studi Komparatif Hak Asasi Manusia Antara Perspektif The Universal Declaration of Human Right dan The Cairo Declaration of Human Right) - Adriana Mustafa (Universitas Islam Negeri Alauddin Makassar, 2020)
The emergence of the term Transgender in Indonesia first appeared in 1860 and underwent development in the 1990s. In 1986 the term Wadam (Female Adam) emerged, but changed into a transsexual (Male Female). The amendment was based on the objection of several parties because of the use of the name of Adam's Woman. It was considered impolite because the name of the Prophet Adam as.In the Universal Declaration of Human Right, there is indeed no mention of sexual orientation, it must be of the opposite sex, what is concerned about human rights to marry and build families, namely article 16 which is then used as a basis by transgender people to justify deviant sexual behavior they are through same-sex marriage. On the other hand, in the Universal Declaration of Human Right there is also article 18 which guarantees the right of everyone to believe in the teachings of his religion and practice his religious teachings well. While we all know there is no religious teaching in this world that allows sexual behavior to deviate, even the most tolerant religion.